Comparative Carcinogenic Effects of Folic Acid vs. 5-Methyltetrahydrofolate Supplementation on Colon Cancer Progression in a Rodent Model. (7th June 2021) - Kaur, Baljit; Chan, Carina; Yim, Samantha; Sohn, Kyoung-Jin; Kim, Young-In
Abstract: Objectives: High folic acid (FA) intake may be associated with adverse health outcomes, including colon cancer promotion. 5-methyltetrahydrofolate (5MTHF) has been proposed as a safer alternative form of folate supplementation. We compared the effects of FA and 5MTHF supplementation on the progression of aberrant crypt foci (ACF; earliest colon cancer precursor). Methods: Male Sprague Dawley rats (n = 120) received a control diet (1mg FA or equimolar 5MTHF) at weaning and ACF were induced by azoxymethane. Six weeks post-induction, rats were randomized to the control or supplemental (10mg FA or equimolar 5MTHF) diets for 18 weeks. Plasma folate concentrations were assessed using microbiological assay and compared. Colorectal tumor incidence, multiplicity and burden (sum of tumor diameters) were determined and compared. Results: 5MTHF resulted in higher plasma folate concentration compared to FA (p < 0.05). Tumor incidence (adenoma, p = 0.5; adenocarcinoma, p = 0.60) did not differ between the folate forms. Both FA and 5MTHF supplementation resulted in a higher number of adenocarcinomas compared to respective controls. 5MTHF groups had higher tumor burden compared to the corresponding levels of FA (p < 0.05). Conclusions: 5MTHF resulted in higher tumor burden than FA and was at least as effective as FA in increasing the number of adenocarcinomas in predisposed rats harboring ACF. 5MTHF does not confer a safer alternative to FA supplementation with regards to colon cancer promotion and may in fact have a higher colon tumor promoting effect than FA supplementation. Notwithstanding the inherent limitations associated with animal models, our study suggests that future studies are warranted to compare biochemical and biologic effects and safety of FA and 5MTHF supplementation. Funding Sources: Canadian Institutes of Health Research.